2019
DOI: 10.1097/gme.0000000000001305
|View full text |Cite
|
Sign up to set email alerts
|

The female sexual function index: reliability and validity in Spanish postmenopausal women

Abstract: Objective: To examine the reliability and validity of the Spanish version of the Female Sexual Function Index (FSFI) and its ability to discriminate between women with and without female sexual dysfunction (FSD) among Spanish postmenopausal women. Methods: A total of 152 postmenopausal women completed the Spanish version of FSFI. Internal consistency, test-retest reliability, and construct validity (exploratory factor analysis) were analyzed. Concurrent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 38 publications
2
16
0
1
Order By: Relevance
“…A recent study by Pérez-Herrezuelo validates the Spanish version of FSFI and also reported decreased sexual function among postmenopausal women [45]. Among the reasons cited for low sexual desire in our study by the women participants, vaginal dryness (35.7%) was the most common.…”
Section: Discussionsupporting
confidence: 55%
“…A recent study by Pérez-Herrezuelo validates the Spanish version of FSFI and also reported decreased sexual function among postmenopausal women [45]. Among the reasons cited for low sexual desire in our study by the women participants, vaginal dryness (35.7%) was the most common.…”
Section: Discussionsupporting
confidence: 55%
“…In our study 70.88% of participants presented sexual dysfunction, which is a lower frequency than reported in previous studies employing the FSFI and carried out among postmenopausal women of similar mean age [32,36]. Such difference may be attributable to the fact that those studies employed the traditional FSFI cut-off point described in a study that dealt with several samples of women of a wide range of ages (18-74 years) [37], while we used a cut-off point specifically indicated for an older population [20].…”
Section: Discussionmentioning
confidence: 90%
“…Domain scores range from 0 (or 1) to 5, and the sum of the scores of all domains generates a total which indicates better sexual function the higher the score. In this study we used the validated version of the Spanish FSFI, with a score <24.95 representing a high risk of sexual dysfunction [20].…”
Section: Female Sexual Functionmentioning
confidence: 99%
“…FSFI has been validated for women with cancer [14]. The Spanish FSFI is a valid and reliable instrument for assessing and discriminating FSD among Spanish postmenopausal women [15].…”
Section: Methodsmentioning
confidence: 99%